EDUCATION MANAGEMENT IN BERINGIN JAYA KINDERGARTEN IN THE FRAMEWORK OF IMPROVING COGNITIVE DEVELOPMENT EARLY CHILDREN - Wedhawati, Ni Kadek Vindi (STAH Dharma Sentana Sulawesi Tengah, 2023)
Early childhood is a nation's asset that needs to be given more attention in terms of education. In order to develop optimally, it is necessary to be trained by participating in both formal and informal education. Beringin Jaya Kindergarten provides services on formal channels that can be followed by children aged 4-6 years who have very different thinking abilities. Thinking abilities or also called cognitive abilities in children occur through different sequences which will later help explain the way children think, store information and adapt to their environment. Cognitive abilities can be realized by educational management based on four basic principles, namely planning, organizing, implementing, and supervising. Planning is carried out by managing the administration, starting from paying school registration fees, determining student savings, uniform payments, and monthly payments. Organizing human resources in learning activities between teachers is done by dividing teachers into two classes. The implementation of learning in Beringin Jaya Kindergarten focuses on increasing children's cognitive development. Efforts to improve children's cognitive abilities is by playing. Supervision at Beringin Jaya Kindergarten consists of kindergarten supervisors, school principals, teachers, and parents of students. Teachers cannot be complete supervisors, because children's development depends on the education of parents at home.